A New Compound (8,9) -Furanyl-Pterocarpan-3-Ol Used for Standardization of Bengkuang (Pachyrhizus erosus) Extract as Sunscreen and Skin Whitening Agent - Lukitaningsih, Endang; Holzgrabe, Ulrike (Indonesian Journal of Cancer Chemoprevention, 2019)
Bengkuang (Pachyrhizus erosus) has been traditionally used as sun screening and skin whitening. The active compounds in bengkuang extract already published included their activities in antioxidant and skin whitening. However, standardization of bengkuang extract has not been studied. This research aims to find out the analysis procedure by High Performance Liquid Chromatography to make standardization bengkuang extract.The first step of this research was collecting bengkuang from Prembun, Central Java, Indonesia in dry season. After cleaning and peeling, bengkuang root was sliced, dried and ground to make powder. Then followed by extraction using Soxhlet in petroleum ether and subsequently in methanol. Methanol extract was evaporated and then partitioned with ethyl acetate-water. Ethyl acetate fraction was evaporated and then separated in open column chromatography using silica gel as stationary phase and a gradient mixture of chloroform-ethyl acetate-methanol as mobile phase. Bio guided fraction method was used for separation and purification to get isolated compounds. The isolated compounds obtained from this fractionation were then elucidated and analyzed their activities.A new compound (8,9-furanyl-pterocarpan-ol) has been selected as a biomarker for extract standardization. The optimum of HPLC condition for standardization consisted of a column (Zorbax SB-C18; i.d. 0.46 cm; 5 μm particle size), mobile phase (gradient elution of MeOH-water) with flow rate of 1 ml/min and detector (UV-detector at 293 nm). The obtained LOD value was 0.51 ± 0.02 µg. The potentials of this compound to absorb UV ray, antioxidant and anti-tyrosinase were 4.018 mAU*S/mml; 2.113±0.001mM (SC50); 7.19±0.11 mM (IC50), respectively.Keywords : bengkuang (Pachyrhizus erosus) extract, (8,9)-furanyl-pterocarpan-3-ol, standardization, sunscreen, skin whitening